(untitled) - Widom, Benjamin (Cambridge, 2002)
This is an introduction to statistical mechanics, intended to be used either in an undergraduate physical chemistry course or by beginning graduate students with little undergraduate background in the subject. It assumes familiarity with thermodynamics, chemical kinetics, the kinetic theory of gases, quantum mechanics and spectroscopy, at the level at which these subjects are normally treated in undergraduate physical chemistry. Highly illustrated with numerous exercises and worked solutions, it provides a concise, up-to-date treatise of statistical mechanics and is ideally suited to use in one semester courses.
Keywords: Statistical mechanics,Cơ học thống kê